First Synthesis of the Inherently Chiral Trans‐4′ Bisadduct of C59N Azafullerene by Using Cyclo‐[2]‐dodecylmalonate as a Tether. Issue 55 (31st August 2021) - Asad, Karam; Stergiou, Anastasios; Kourtellaris, Andreas; Tagmatarchis, Nikos; Chronakis, Nikos
Abstract: The multiaddition chemistry of azafullerene C59 N has been scarcely explored, and the isolation of pure bisadducts is in its infancy. Encouraged by the recent regioselective synthesis of the inherently chiral equatorialface bisadduct of C59 N, we focused on the isolation of the first trans‐ 4 bisadduct in a simple two‐step approach. The first regioselective synthesis of the trans‐ 4 bisadduct of C59 N by using cyclo‐ [2]‐dodecylmalonate as a tether is now reported. The newly synthesized bisadduct has C 1 symmetry, as evidenced by 13 C NMR, while X‐ray crystallography validated the trans‐ 4′ addition pattern. Furthermore, the inherently chiral trans‐ 4′ C59 N bisadduct was enantiomerically resolved, and the mirror‐image relation of the two enantiomers was probed by circular dichroism spectroscopy. Finally, UV‐Vis and redox assays suggested that the addition pattern has a reflection in the light‐harvesting and redox properties of the bisadduct. Abstract : Heterofullerene tailoring : The inherently chiral trans ‐4′ bisadduct of azafullerene has been synthesized. X‐ray crystallography validated the trans‐ 4′ addition pattern, and 13 C NMR spectroscopy showed C 1 symmetry. The bisadduct was enantiomerically resolved, and the mirror‐image relation of the enantiomers was probed by CD spectroscopy. The UV‐Vis absorption and electrochemical data suggest that the addition pattern has a reflection in the light‐harvesting and redox properties of the bisadduct as compared to the equatorialface bisadduct.